Cutting edge: nonglycosidic CD1d lipid ligands activate human and murine invariant NKT cells. - Silk, J; Salio, M; Reddy, BG; Shepherd, D; Gileadi, U; Brown, J; Masri, S; Polzella, P; Ritter, G; Besra, G; Jones, E; Schmidt, R; et al. (2008)
Invariant NKT cells (iNKT cells) recognize CD1d/glycolipid complexes. We demonstrate that the nonglycosidic compound threitolceramide efficiently activates iNKT cells, resulting in dendritic cell (DC) maturation and the priming of Ag-specific T and B cells. Threitolceramide-pulsed DCs are more resistant to iNKT cell-dependent lysis than alpha-galactosylceramide-pulsed DCs due to the weaker affinity of the human iNKT TCR for CD1d/ threitolceramide than CD1d/alpha-galactosylceramide complexes. iNKT cells stimulated with threitolceramide also recover more quickly from activation-induced anergy. Kinetic and functional experiments showed that shortening or lengthening the threitol moiety by one hydroxymethylene group modulates ligand recognition, as human and murine iNKT cells recognize glycerolceramide and arabinitolceramide differentially. Our data broaden the range of potential iNKT cell agonists. The ability of these compounds to assist the priming of Ag-specific immune responses while minimizing iNKT cell-dependent DC lysis makes them attractive adjuvants for vaccination strategies.